2008
DOI: 10.1096/fj.07-097774
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein misfolding and amyloidogenesis

Abstract: In early atherogenesis, subendothelial retention of lipidic droplets is associated with an inflammatory response-to-injury, culminating in the formation of foam cells and plaque. Low density lipoprotein (LDL) is the main constituent of subendothelial lipidic droplets. The process is believed to occur following LDL modification. Searching for a modified LDL in plasma, electronegative LDL [LDL(-)] was identified and found to be associated with major risk biomarkers. The apoprotein in LDL(-) is misfolded, and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 37 publications
(46 reference statements)
3
42
1
2
Order By: Relevance
“…This process was paralleled by phospholipid degradation. These results concur with previous studies reporting that in the absence of physical or chemical stimuli, total LDL(Ϫ) aggregates to form amyloid-like fibrils in a period of one to several days and that it can promote the spontaneous aggregation of native LDL (18). Our results suggest that amyloidogenesis promoted by LDL(Ϫ) could be specifically due to agLDL(Ϫ) in a process involving PLC-like activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This process was paralleled by phospholipid degradation. These results concur with previous studies reporting that in the absence of physical or chemical stimuli, total LDL(Ϫ) aggregates to form amyloid-like fibrils in a period of one to several days and that it can promote the spontaneous aggregation of native LDL (18). Our results suggest that amyloidogenesis promoted by LDL(Ϫ) could be specifically due to agLDL(Ϫ) in a process involving PLC-like activity.…”
Section: Discussionsupporting
confidence: 93%
“…Studies performed in endothelial and mononuclear cells have shown that LDL(Ϫ) induces inflammation and apoptosis and impairs angiogenesis (11)(12)(13)(14). Regarding its physicochemical characteristics, apolipoprotein B-100 (apoB) in LDL(Ϫ) presents structural differences versus apoB in native LDL (15), binds poorly to the LDL receptor (16), is prone to aggregation (17), and presents amyloidogenic properties (18). Our group recently reported that LDL(Ϫ) has several populations with normal or high binding affinity to proteoglycans compared with native LDL (1).…”
mentioning
confidence: 99%
“…The binding of apoJ to unfolded proteins promotes its recognition by LDL-receptor-related protein 2 (LRP2) and favors its clearance and degradation ( 30 ). Interestingly, LDL( Ϫ ) presents some structural abnormalities, including particle aggregation ( 32 ) and apoB misfolding ( 33,34 ), that could be related to the presence of apoJ in this subfraction.…”
Section: Discussionmentioning
confidence: 99%
“…303) During aggregation, a dominostyle spread of apoB-100 misfolding from LDL(−) to all of the LDL particles occurs. 303) It has been predicted that a structure in the α 2 domain is highly prone to a conformational switch from a native α-helical arrangement toward cross-β aggregation with other protein molecules.…”
Section: Apob Denaturationmentioning
confidence: 99%
“…307) However, the overall secondary structure of lipid-free apoB is highly conserved, suggesting the solubilization of lipid-free apoB by NaDC may lead to only partial unfolding of the secondary structure in apoB rather than global protein unfolding as shown in oxLDL or LDL(−). 299,300,303,307,308) I have investigated the cytotoxic effect of lipid-free apoB solubilized with NaDC, as a model for denatured apoB. Lipidfree apoB has cytotoxicity to J774 macrophages, HepG2 cells and Chinese hamster ovary cells, whereas LDL-apoB and lipid-free apoA-I have no effect on the cell viability.…”
Section: Apob Denaturationmentioning
confidence: 99%